2020
DOI: 10.3390/ani10010160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transport Conditions on Behavioural and Physiological Responses of Horses

Abstract: The regulations for minimal space and direction of travel for land transport in horses vary worldwide and there is currently no definitive guidance to promote equine health and welfare. This study evaluated the effects of bay size and direction of travel (forwards/backwards) in horses by comparing the behavioural, physiological, laboratory and gastroscopy parameters between transported and confined horses. A total of twenty-six mares took part in the study; 12 horses were confined for 12 h, and all mares under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
(65 reference statements)
0
22
0
Order By: Relevance
“…The effects of transportation on the welfare of horses include anxiety-related behaviours, aggression, exhaustion, injury, respiratory and gastrointestinal disease, dehydration, pyrexia, and immunosuppression [ 3 , 9 , 10 ]. About 1% of horses die en route [ 4 ] but a greater percentage of animals are euthanised later due to severe injuries sustained during the journey or have non-visible injuries such as bruising, which is only recognisable post-mortem [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of transportation on the welfare of horses include anxiety-related behaviours, aggression, exhaustion, injury, respiratory and gastrointestinal disease, dehydration, pyrexia, and immunosuppression [ 3 , 9 , 10 ]. About 1% of horses die en route [ 4 ] but a greater percentage of animals are euthanised later due to severe injuries sustained during the journey or have non-visible injuries such as bruising, which is only recognisable post-mortem [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Takahashi et al [ 9 ] found that showering with tap water was the most effective method to decrease the temperature in horses. The horse body temperature is also considered in the context of assuring good welfare conditions affecting the performance in different horses at rest, during effort, and in transport [ 10 , 11 ]. Horses released freely into a paddock have mainly been studied with regard to their relaxation [ 12 ], behaviour [ 13 , 14 ], and preferences for the time spent out of the stable [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…During transport, pigs are subjected to many adverse situations including weather conditions [ 1 ]. Several studies focused on the influence of factors related to transport including loading density, handling treatment, trailer design, loading method, environmental and internal climate conditions, duration of the journey [ 4 , 5 , 6 ]. Regarding duration, journeys are divided into short (<8 h) and long journeys (>8 h) although the Member States may grant derogations for journeys not exceeding 12 h to reach the final place of destination [ 7 ].…”
Section: Introductionmentioning
confidence: 99%